EXPLORING THE ROLE OF HIJAB IN FOSTERING PERSONAL SECURITY AND POSITIVE BODY IMAGE: A Cross-Cultural Analysis of Indonesian and Pakistani Women's Perspectives (JOURNAL OF INDONESIAN ISLAM, 2024)
This study explores the impact of the hijab on women's personal security, body image, and cultural perceptions in Indonesian and Pakistani contexts. Twenty-three female participants, aged 15-50, who regularly wear the hijab, participated in semi-structured interviews selected through purposive sampling. Thematic analysis of the interviews highlighted the hijab's role in providing safety and protection, influenced by cultural norms and the Islamic principle of ‘Wajib’ (obligatory practice). Both Pakistani and Indonesian women perceived the hijab as enhancing beauty, modesty, and comfort, challenging stereotypes and empowering women. Indonesian participants reported encountering job-related challenges due to hijab requirements, while Pakistani women faced fewer such obstacles. Overall, the hijab was positively perceived in both societies, symbolizing religious devotion, personal choice, and cultural significance. This research addresses a significant gap by examining the hijab's influence on personal security and body image among Indonesian and Pakistani women, contributing valuable insights into lesser-known aspects of hijab perception.